Sosialisasi Penerapan Algoritma Media Sosial Youtube untuk Menaikkan Jumlah Pengunjung - Rahman Abdillah; Ibnu Adkha; Dwi Puspita Agustin; Nur Alam (Fakultas Teknik Universitas Maritim AMNI Semarang, 2025)
YouTube is one of the leading video-based social media platforms with a complex algorithm for recommending content to users. Understanding this algorithm is crucial for content creators to increase visitor numbers and audience engagement. This socialization activity aims to educate beginner content creators on video optimization strategies to enhance discoverability and recommendation by YouTube’s system. The socialization was conducted online via Zoom, utilizing presentations, interactive discussions, and simulations of YouTube Studio features. The results of this activity indicate an improvement in participants’ understanding of key factors influencing the YouTube algorithm, such as watch duration, user interactions, and metadata optimization. Some participants who implemented the taught strategies experienced up to a 30% increase in video views within a month. However, challenges remain in maintaining content consistency and utilizing YouTube analytics effectively. Therefore, continuous mentoring is necessary to help participants refine more effective strategies. This socialization is expected to enable content creators to maximize the YouTube algorithm to enhance their channel visibility and growth.